An experimental study of the electrical activity of the bypassed stomach in the Roux-en-Y gastric bypass - Ferraz,Álvaro Antônio Bandeira (2007)
BACKGROUND: Surgical options for morbid obesity are diverse, and the Roux-en-Y gastric bypass, initially described by Fobi has gained popularity. Knowledge about the physiology of the bypassed stomach is limited because this newly produced segment of the stomach is inaccessible to endoscopic or contrast radiological studies. AIM: To evaluate the myoelectric activity of the bypassed stomach and its reply to the feeding. METHODS: An experimental protocol was conducted to evaluate postoperative gastric bypassed motility in dogs submitted to the Roux-en-Y gastric bypass procedure. Two groups of five animals were studied on postoperative fasting and after a standard meal, recording electrical response and control activity. Both control and Roux-en-Y gastric bypass operated study group had a pair of electrodes placed on three points of the remaining stomach: fundus, body and antrum. Data registration was performed after complete ileus resolution, and analysed with DATA Q Inst. series 200. RESULTS: The results achieved on the conditions of this study suggest that: 1. the remaining stomach maintain the same pattern of motility; 2. there is a reduced fasting electromyography activity following the Roux-en-Y gastric bypass procedure; 3. significantly reduced fasting electric control activity when compared both groups, and a markedly reduced fasting response electric activity and; 4. the electric response to the feeding kept the same standard of the stomach, however in a statistically reduced way. CONCLUSION: The electrical activity of the bypassed stomach of Roux-en-Y gastric bypass procedure kept the same pattern but in a statistically reduced number of contraction.